MPS 17-03 A unique model for capacity building of primary care physicians in management of chronic conditions in India. (September 2016) - Bhalla, Sandeep; Unnikrishnan, Ranjit; Unnikrishnan, Ambika G.; Mohan, Viswanathan; Tandon, Nikhil; Prabhakaran, Dorairaj
Abstract : Objective: To describe the model adopted for the capacity building of PCPs in management of chronic conditions in India. Design and Method: An innovative collaborative model between Public Health Foundation of India (PHFI), Delhi and academic partners supported by an educational grant from a stakeholder was designed. The initiatives were implemented with an objective to enhance knowledge, skills and core competencies of Primary Care Physicians (PCP) in the management of chronic conditions. An evidence based curriculum was developed by the academic partners and was later reviewed by national experts in their respective fields. Regional faculties that are specialists in the field delivered the course content to the PCPs. The course comprises of didactic lectures, case studies and instructional videos. We established a strong monitoring and evaluation mechanism comprising of on-site random visits by a team of observers who were drawn from a national pool of public health experts. Results: Seven initiatives have been implemented so far on various chronic conditions including diabetes mellitus, thyroid disorders, hypertension, COPD & asthma. More than 11, 500 participants from 531 of the 676 districts (78%) in India have been enrolled in these initiatives till date. The mean age of participants enrolled is 39 years with a clinical experience of 13 years. Over 30% of the participants were affiliated to public sector and 38 % were post- graduates (MD/MS/DNB). The model has been accepted by various state governments for training their medical officers. Some of these programs have received recognition from the International Diabetes Federation & South Asian Federation of Endocrine Societies. One of the initiatives was the finalist in the excellence in medical education category of BMJ awards India, 2014. Conclusions: The success of this model in the Indian setting implies its use in other developing countries with similar backgrounds to effectively manage the increasing burden of chronic conditions.